Recurrent sick leave and resignation rates among female cancer survivors after return to work: the Japan sickness absence and return to work (J-SAR) study - Motoki Endo (BMC Public Health, 2019)
Abstract Background To date, there have not been any workforce-based Japanese cohort studies investigating work sustainability after return to work (RTW). The objective of this study was to investigate the post-RTW cumulative recurrent sick leave rate and cumulative resignation rate among female cancer survivors. Methods Among Japanese employees who were registered in the Japan sickness absence and return to work (J-SAR) study, the subjects were those female employees who returned to work after sick leave due to newly clinically diagnosed cancer (C01-C99; ICD-10), based on a physician’s certificate, between 2000 and 2011. The last day of the follow-up period was December 31, 2012. The recurrent sickness leave rate and resignation rate were calculated using competing risk survival analysis. Results Of 223 cancer survivors, 61 took further physician-certified sick leave after their RTW. The median duration of the post-RTW work period among all cancer survivors was 10.6 years. The work continuance rates of the female cancer survivors were 83.2 and 60.4% at 1 and 5 years after they returned to work, respectively. There was a steep reduction in the work continuance rate during the first post-RTW year. There were considerable differences in the work continuance rate according to the primary cancer site. Cumulative recurrent sick leave rates of 11.8 and 28.9% were seen at 1 and 5 years after the subjects returned to work. The cumulative resignation rate was 5.0 and 10.7% at 1 and 5 years after the subjects returned to work. Most recurrent sick leave occurred in the first year after the subjects returned to work, followed by the second year. Conclusions Sixty percent of female cancer survivors were still working at 5 years after returning to work, although the work continuance rates for different types of cancer varied significantly.